Analyisis of Marketing for Export Products of Coconut Shell Charcoal Briquettes - Sauqy, Muhammad Syafiqus; Iryanti, Endang (CV. Lenggogeni Data Publishing, 2023)
This research contains an analysis of the marketing mix strategy towards the export of coconut shell charcoal briquette products. This research, which uses a qualitative study method, aims to provide information to briquette charcoal business actors on the export potential of briquette charcoal with a marketing mix strategy approach and SWOT analysis results. The results of this study provide the convenience obtained in marketing briquetted charcoal products effectively and efficiently